TO THE QUESTION OF SEARCH FOR UPBRINGING THOUGHTS IN THE ANALYSIS OF PUBLICATIONS ON ISLAMIC CULTURE - Kadyrov, K.B. (ILIM hám JÁMIYET, 2020)
The article examines the educational thoughts of various publication sources in the analysis of Islamic culture, the author analyzes the scientific work and thoughts of specialists in this field.